2021
DOI: 10.12659/msm.929280
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Sociodemographic and COVID-19-Related Factors: The Association Between the Need for Psychological and Information Support from School and Anxiety and Depression

Abstract: Background In addition to sociodemographic and COVID-19- related factors, the needs of school support, including material, psychological and information support, have seldom been discussed as factors influencing anxiety and depression among college students during the COVID-19 pandemic. Material/Methods In this cross-sectional study, 3351 college students from China were surveyed through questionnaires about their sociodemographic and COVID-19 characteristics, the needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Table 1 shows the overall characteristics of the 41 included studies ( Elhadi et al, 2020 ; Jindal et al, 2020 ; Liu et al, 2020 ; Medeiros et al, 2020 ; Muhammad Alfareed Zafar et al, 2020 ; Nadeem et al, 2020 ; Nakhostin-Ansari et al, 2020 ; Nihmath Nisha et al, 2020 ; Sartorao Filho Carlos et al, 2020 ; Sun et al, 2020 ; Adhikari et al, 2021 ; Banstola et al, 2021 ; Basheti et al, 2021 ; Bilgi et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Gupta et al, 2021 ; Halperin et al, 2021 ; Kalkan Uğurlu et al, 2021 ; Kaplan Serin and Doğan, 2021 ; Keskin, 2021 ; Kuman Tunçel et al, 2021 ; Li et al, 2021 ; Mekhemar et al, 2021 ; Meng et al, 2021 ; Nishimura et al, 2021 ; Patelarou et al, 2021 ; Pavan et al, 2021 ; Pelaccia et al, 2021 ; Perissotto et al, 2021 ; Saeed and Javed, 2021 ; Safa et al, 2021 ; Song et al, 2021 ; Xiao et al, 2021 ; Xie et al, 2021 ; Yadav et al, 2021 ; Yang et al, 2021 ; Yin et al, 2021 ; Zhang et al, 2021a ; Zheng et al, 2021 ; Zhu et al, 2021 ). On the whole, 40 cross-sectional studies and 1 longitudinal study were included in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the overall characteristics of the 41 included studies ( Elhadi et al, 2020 ; Jindal et al, 2020 ; Liu et al, 2020 ; Medeiros et al, 2020 ; Muhammad Alfareed Zafar et al, 2020 ; Nadeem et al, 2020 ; Nakhostin-Ansari et al, 2020 ; Nihmath Nisha et al, 2020 ; Sartorao Filho Carlos et al, 2020 ; Sun et al, 2020 ; Adhikari et al, 2021 ; Banstola et al, 2021 ; Basheti et al, 2021 ; Bilgi et al, 2021 ; Gao et al, 2021 ; Guo et al, 2021 ; Gupta et al, 2021 ; Halperin et al, 2021 ; Kalkan Uğurlu et al, 2021 ; Kaplan Serin and Doğan, 2021 ; Keskin, 2021 ; Kuman Tunçel et al, 2021 ; Li et al, 2021 ; Mekhemar et al, 2021 ; Meng et al, 2021 ; Nishimura et al, 2021 ; Patelarou et al, 2021 ; Pavan et al, 2021 ; Pelaccia et al, 2021 ; Perissotto et al, 2021 ; Saeed and Javed, 2021 ; Safa et al, 2021 ; Song et al, 2021 ; Xiao et al, 2021 ; Xie et al, 2021 ; Yadav et al, 2021 ; Yang et al, 2021 ; Yin et al, 2021 ; Zhang et al, 2021a ; Zheng et al, 2021 ; Zhu et al, 2021 ). On the whole, 40 cross-sectional studies and 1 longitudinal study were included in our study.…”
Section: Resultsmentioning
confidence: 99%
“…According to the methodological quality evaluation of the literature by two researchers, forty studies were of moderate quality, one of high quality ( Meng et al, 2021 ), and one of low quality ( Nadeem et al, 2020 ). Our meta-analysis will not include low quality studies ( Supplementary Material 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, students surfing the internet for a long time will be able to obtain more accurate details about COVID-19, which can prevent misunderstanding relevant information. Nevertheless, individuals with shorter browsing times often have a higher risk for depression given that they may be easily misled by the rumors and have limited time to verify the authenticity of relevant information[ 64 ]; (3) Academic stress increases the degree of depression of college students with the closure of schools, the challenges of online courses and the risk of graduation delay[ 13 , 65 ]; (4) Financial pressures include the impact of the pandemic on family economic resources[ 49 ] and the increasing uncertainty of individuals about future employment[ 13 ]; (5) Environmental changes, home study, self-isolation, isolation from relatives and friends, decreased exercise frequency, uncertainty of school reopening, regular temperature measurement, wearing masks for a long time, cancellation of package deliveries and take-out supplies and other forced changes in daily study and living habits all increase the risk of depression among college students[ 13 , 49 ]; (6) There is less family support, social support and deteriorating family relations[ 65 ]; and (7) Social confidence wanes. Research has shown that the prevalence of depression also increases when individuals lack confidence in the government[ 66 ].…”
Section: Nonpathological Influencing Factors Of Depressionmentioning
confidence: 99%
“…(2) Individuals who isolate themselves have higher rates of depression, irritability, and loneliness. Meng et al, 2021 29 Anxiety, depression Survey and Cross-sectional study of 3 351 college students in China, in relation to sociodemographic and COVID-19 characteristics, the needs of school support and mental wellbeing (1) Students are increasingly reliant on schools for psychological and informational support. (2) Using methods to learn about the COVID-19 pandemic, such as online curricula and books, can help to reduce anxiety and depression.…”
Section: Methodsmentioning
confidence: 99%